Penanganan Perkara Tindak Pidana Narkotika Yang Di Lakukan Oleh Prajurit TNI Angkatan Laut - Sutejo; Saleh, Mohammad (Dinasti Review Publisher, 2024)
The involvement of Navy soldiers in narcotics and Psychotropic crimes requires consistent efforts for their prevention and eradication. The consistency of the TNI leadership in efforts to prevent the involvement of TNI soldiers in narcotics and Psychotropic crimes is carried out by issuing regulations, either in the form of Telegram letters (ST) of the TNI commander or decisions of the Chief of Naval Staff. For Navy soldiers who are proven to be involved in abuse, depositors, dealers and manufacturers of narcotics and Psychotropic Substances must be held legally responsible. As for the form of responsibility, it also varies depending on the degree of guilt, it starts to be rehabilitated, the investigation process is carried out by the pom TNI, until the case is submitted to military justice and is proposed to be fired. The purpose of this study was to analyze the handling of cases of narcotics and Psychotropic crimes committed by Navy soldiers and law enforcement against cases of narcotics and Psychotropic crimes committed by Navy soldiers.